2011
DOI: 10.1007/s11368-011-0352-5
|View full text |Cite
|
Sign up to set email alerts
|

Carbon metabolism of soil microbial communities of restored forests in Southern China

Abstract: Purpose The structure and dynamics of carbon metabolic process of the soil microbial community in restored forests were dependent on the methods employed in reforestation and subsequent management. To find an appropriate method to restore degraded forests and to assess the ecological benefits of restorations, we studied community level physiological profiles of soil microbial communities in forests in Southern China that were restored by three different methods. Materials and methods Community level physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…Carbon metabolism function of the soil microbial community is closely related to the nutrient cycle process of forest ecosystems. Lower carbon metabolism function in a soil microbial community indicates a degradation trend in a forest or soil ecosystem (Zheng et al, 2005;Wang et al, 2011). In our study, lower carbon metabolism function of the soil microbial community in the Eucalyptus plantations suggests a decrease in soil quality, soil microbial diversity, and even ecosystem function following plantation conversion.…”
Section: Comparison Of Soil Microbial Composition and Function Betweementioning
confidence: 54%
“…Carbon metabolism function of the soil microbial community is closely related to the nutrient cycle process of forest ecosystems. Lower carbon metabolism function in a soil microbial community indicates a degradation trend in a forest or soil ecosystem (Zheng et al, 2005;Wang et al, 2011). In our study, lower carbon metabolism function of the soil microbial community in the Eucalyptus plantations suggests a decrease in soil quality, soil microbial diversity, and even ecosystem function following plantation conversion.…”
Section: Comparison Of Soil Microbial Composition and Function Betweementioning
confidence: 54%
“…Consistent with these observations, our results clearly showed that the enhanced metabolic capacity for carbohydrates in soils amended with BIO was also benefitable for the plant’s defense against Fusarium wilt. The PCA and kinetics analysis, both demonstrated that the lower carbon metabolism function was observed in CK rhizosphere soils along with the planting years, which indicated a degradation trend in a soil ecosystem39. In contrast, the stable general microbial metabolic potential was detected in fields applied by BIO.…”
Section: Discussionmentioning
confidence: 95%
“…Wang et al (2008Wang et al ( , 2011) also used these two methods to investigate the effects of fertilization on bacterial community structure and function in black soils. The microbial metabolic activity in konjac soils was described by AWCD of substrates arranged on the BIOLOG EcoPlate.…”
Section: Discussionmentioning
confidence: 99%